Strength of Cement Treated Clay and Degradation Under Magnesium Sulphate Attack - Vicky Marita Siregar; Luky Handoko; Sumiyati Gunawan (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2019)
Lumpur Sidoarjo (Lusi) is an environmental issue in Indonesia that produce wasted soils, specifically clay soils, distributed to Porong River which causes a greater problem. Cement treated clay (CTC) becomes one of the solutions to overcome the problems caused by Lusi due to its ability in improving the strength of clay soils. This paper investigates CTC with lower cement amount (C <70 kg/m3) for reclamation and higher cement amount (C >150 kg/m3) for deep mixing marine clay for its strength and degradation due to the attack of magnesium sulphate as the main component of seawater which cause the degradation of CTC. The enhancement of soil strength is investigated by unconfined compression test (qu) and the degradation by penetration test. Water content of the specimens for both tests are arranged in its liquid limit condition (60%) and two times of its LL (120%). The result of the cement amount addition for both water content shows the enhancement of qu represented by linear and the tip resistance is increased. The characterictic of degradation for lower cement amount with close range present similar depth of deterioration, like-wise higher cement content. The value of tip resistance is not relatable with qu.